PELATIHAN PEMANFAATAN BARANG BEKAS UNTUK PEMBUATAN BUKET BUNGA DAN CARA PEMASARANNYA - Indah Puji Astuti; Ghulam Asyrofi Buntoro; Dwiyono Ariyadi (WARTA LPM, 2019)
Waste is one of the problems that often arise in life society. However, many ways are considered wiser in solving problems with garbage. One of them is by using it to produce new products that have economic value. Not only can it reduce the garbage stack, but this method can also bring additional income. This service activity was carried out in the village of Bulu Lor, Jambon Subdistrict, Ponorogo Regency. Aim to provide training in making a bouquet by utilizing used items to homemakers and their youth. Besides, it also teaches how to market handicraft products to be known to more quickly, so the possibility of selling products is getting bigger. The result of this activity is to increase entrepreneurial skills to the community by providing capabilities to homemakers and youth in making flower bouquets and teaching how to market product results online. Keywords: Waste, bucket flower, entrepreneurship, online marketing